Peran Pengaruh Green Accounting terhadap Likuiditas, Profitabilitas, dan Leverage Perusahaan pada PT Indocement Tunggal Prakarsa Tbk Periode 2020-2022 - Amalia, Devina Shava; Pratiwi, Anggun; Salsabila, Sausan Nada; R. Pandin, Maria Yovita (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
Knowing whether or not there is an effect of green accounting on the entity's liquidity, profitability, and leverage is the purpose of this study. The sample of this study is one cement producer entity listed on the IDX from 2020 to 2022, namely PT Indocement Tunggal Prakarsa Tbk. The data used comes from the annual report and sustainability report of the entity PT Indocement Tunggal Prakarsa Tbk for the period 2020-2022. The hypothesis test used in this study is a simple linear regression analysis test using the SPSS program. Liquidity, profitability and leverage are dependent variables with environmental costs as independent variables. The analysis results show that although environmental cost is an indicator of green accounting, this cost has no significant impact on the entity's financial performance indicators, such as liquidity, profitability, and leverage.